Roman pilgrimage : the station churches - Weigel, George, 1951- (Basic Books, a member of Perseus Books Group, 2013)
Theologian and papal biographer George Weigel, art historian Elizabeth Lev, and photographer Stephen Weigel explore the annual Lenten pilgrimage to dozens of Rome's most striking churches, which for many faithful is a sacred tradition dating back almost two millennia, to the earliest days of Christianity. Along this historic spiritual pathway, today's pilgrims confront the mysteries of the Christian faith through a program of biblical and early Christian readings amplified by some of the greatest art and architecture of western civilization.